THE CURRENT PROBLEMS AND SETTLEMENT DYNAMICS ANALYSIS IN RA MOUNTAINOUS AND HIGH MOUNTAINOUS AREAS (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Settlement dynamics tendencies during last three decades in RA mountainous and high mountainous areas were given based on the analysis and generalization of factual and statistical data. The problems connected with them have been revealed in the article. The research was done on the basis of permanent and current, rural and urban population, rural settlements population number, as well as population distribution by elevation zones.
Keywords: mountainous areas; settlement; dynamics; population number; rural population; urban population